Respostas

2014-07-22T23:14:16-03:00
Olá, Deboralavareda!

1) y² - 4y + 3 = 0
a = 1
b = -4
c = 3
Δ = b² - 4.a.c
Δ = (-4)² - 4.1.3
Δ = 16 - 12
Δ = 4

-b +- √Δ / 2.a
-(-4) +- √4 / 2.1
4 +- 2/2

x' = 4+2/2 = 6/2 =3
x'' = 4-2/2 = 2/2 = 1
S = {3, 1}

2) n² + 4n - 12 = 0
a = 1
b = 4
c = -12
Δ = b² - 4.a.c
Δ = 4² - 4.1.(-12)
Δ = 16 + 48
Δ = 64

-b +- √Δ / 2.a
-4 +- √64 / 2.1
-4 +- 8 / 2

x' = -4+8/2 = 4/2 = 2
x'' = -4-8/2 = -12/2 = -6

S = {2, -6}

3) r² - 2r - 3 = 0
a = 1
b = -2
c = -3
Δ = b² - 4.a.c
Δ = (-2)² - 4.1.(-3)
Δ = 4 + 12
Δ = 16

-b +- √Δ / 2.a
-(-2) +- √16 / 2.1
2 +- 4 / 2

x' = 2+4/2 = 6/2 = 3
x'' = 2-4/2 = -2/2 = -1

S = {3, -1}
1 4 1
como sei que a=1 b=-4 e c=3 ?
São os coeficientes da expressão.
como assim ?